Factors influencing the decision to visit tourists to Tanah Lot, BALI province - Dadang Hermawan; Ni Made Dewi Kansa Putri (Institute of Computer Science (IOCS), 2022)
Post-pandemic tourism activities in Indonesia have started to improve as indicated by the increasing number of visits. It is also feltby the Province of Bali, especially in the Tanah Lot tourist destinationwhich has become a tourism icon of pride in the province of Bali. The attractions offered can be a driving force for tourists to visit. The decision of tourists to visit is the most important aspect that can increase tourism revenue. Therefore, the decision to visit tourists must be increased through the factors that influence it. Based on these reviews, this study aims to examine and analyze the influence of e-Wom, tourist facilities, and implementation of health protocols on tourists' visiting decisions to Tanah Lot, Bali Province. This research is an associative quantitative study with a sample of 400 tourists visiting Tanah Lot, Bali Province. The data analysis technique uses partial least square analysis. The results of the study concluded that e-Wom and implementation of health protocols had a significant effect on visiting decisions, while tourist facilities did not have a significant effect on visiting decisions.